Analisis Kelayakan Pembukaan Mini Resto Kayoemanis di Kota Cilegon - Velvia, Adhelia Dwi Octizara; Chumaidiyah, Endang; Aryani, Sinta (Innovative: Journal Of Social Science Research, 2024)
Kayoemanis is a food business engaged in the food and beverage industry that sells snacks such as dimsum. Kayoemanis has been established since 2021 and is located in Cilegon City. Kayoemanis still produces at the owner's house and does not officially have a mini restaurant, so Kayoemanis plans to open a mini restaurant. This study aims to determine market demand, operational technical design, financial feasibility and sensitivity level of opening a Kayoemanis mini restaurant in Cilegon City. The stages in carrying out this research consist of the preliminary stage, data collection stage, data processing stage, analysis stage, and ending with the conclusion and suggestion stage. Based on the feasibility calculation in the financial aspect, the NPV was obtained of IDR 248,023,814, IRR of 54.43% with PBP for 2.95 years. Furthermore, a sensitivity analysis calculation was carried out with an increase in raw material costs, a decrease in selling prices, and a decrease in market demand. The opening of the Kayoemanis mini restaurant is sensitive to the increase in raw materials by 54.51%, the decrease in selling prices by 26.30%, and the decrease in market demand by 6.82% so that the opening of the Kayoemanis mini restaurant in Cilegon City can be said to be feasible.